Salivary gland proteins of the human malaria vector, Anopheles dirus B (Diptera: Culicidae) - Narissara Jariyapan (2018)
Salivary gland proteins of the human malaria vector, Anopheles dirus B were determined and analyzed. The amount of salivary gland proteins in mosquitoes aged between 3 - 10 days was approximately 1.08 ± 0.04 μg/female and 0.1 ± 0.05 μg/male. The salivary glands of both sexes displayed the same morphological organization as that of other anopheline mosquitoes. In females, apyrase accumulated in the distal regions, whereas alpha-glucosidase was found in the proximal region of the lateral lobes. This differential distribution of the analyzed enzymes reflects specialization of different regions for sugar and blood feeding. SDSPAGE analysis revealed that at least seven major proteins were found in the female salivary glands, of which each morphological region contained different major proteins. Similar electrophoretic protein profiles were detected comparing unfed and blood-fed mosquitoes, suggesting that there is no specific protein induced by blood. Two-dimensional polyacrylamide gel analysis showed the most abundant salivary gland protein, with a molecular mass of approximately 35 kilodaltons and an isoelectric point of approximately 4.0. These results provide basic information that would lead to further study on the role of salivary proteins of An. dirus B in disease transmission and hematophagy.